An Evaluation Of Prophylactic Tranexamic Acid's Ability To Stop Postpartum Hemorrhage: A Systematic Review - Mutia Juliana (The Indonesian Journal of General Medicine, 2024)
Background: Tranexamic acid (TXA) has been used to treat acute bleeding in trauma-related settings, with low side effects. However, the benefits of prophylactic TXA use remain unclear, raising the possibility of administration before PPH diagnosis. Methods: The study followed the PRISMA 2020 guidelines and developed a systematic review and meta-analysis of blinded and randomized clinical trials to determine the impact of prophylactic TXA use on bleeding volume in cesarean or vaginal deliveries, focusing on English studies. Result: TXA showed significant effects on post-partum bleeding reduction, with lower hemoglobin variation compared to the control group. However, some studies reported mild side effects and the effect was even greater in cesarean delivery. Risk factors for bleeding were considered. Conclusion: Promising outcomes have been observed in lowering blood component requirements and preventing postpartum hemorrhage (PPH) with TXA, a prophylactic treatment for PPH. Even though the use of uterotonics was reduced, a recent multicenter RCT conducted in France was unable to demonstrate a meaningful decline in PPH diagnoses. The study also showed a great deal of variability in TXA use and how it affected cesarean deliveries.